Virus and Malware Attacks: A Literature Study on Ethical Issues in Information Technology - celvine adi putra celvine (Institute of Information Technology and Social Science (IITSS), 2023)
The rapid development of information technology has provided significant benefits for communication, education, and business operations. However, it also introduces serious security and ethical challenges, particularly related to the spread of viruses and malware. This study aims to examine the ethical problems and impacts of virus and malware attacks through a comprehensive literature review. The findings reveal that unethical use of technology, negligence in security practices, and cybercrime motives are major contributing factors to malware proliferation. Ethical awareness, combined with strict cybersecurity policies and user education, is essential in mitigating these risks. This paper contributes to the discourse on digital ethics by emphasizing the shared moral responsibility of users, developers, and organizations in maintaining information integrity and security.